School Closures and Student Contact Patterns - Jackson, Charlotte (Centers for Disease Control and Prevention, 2011)
To determine how school closure for pandemic (H1N1) 2009 affected students’ contact patterns, we conducted a retrospective questionnaire survey at a UK school 2 weeks after the school reopened. School closure was associated with a 65% reduction in the mean total number of contacts for each student.